A nação pela pedra: coleções de paleontologia no Brasil, 1836-1844 - Martinez, Paulo Henrique [UNESP] (Casa de Oswaldo Cruz, Fundação Oswaldo Cruz, 2012)
A formação e o estudo de coleções de história natural e de paleontologia participaram da instauração da ordem política do Império do Brasil, delineando também uma ordem científica. A simbiose entre ciência e nação encontrou em Peter W. Lund, iniciador dos estudos de paleontologia em nosso país, um agente ativo e constante. As coleções e escritos desse naturalista deram amparo à visualização do passado e à escrita da história em museus, instituições científicas e culturais brasileiras e europeias. As disputas pelo ordenamento político sob as Regências e a Maioridade foram acompanhadas de perto pelo estudo e a explicação das formas de vida e do globo no passado.

The formation and study of natural history and paleontology collections was part of the installation of political order under the Empire of Brazil, as well as the establishment of a scientific program. The symbiosis between science and the nation was actively promoted by Peter W. Lund, pioneer of paleontology studies in the country. The collections and writings produced by the naturalist lent support to the visualization of the past and the writing of history in Brazilian and European scientific and cultural institutions and museums. The disputes over the political order under the Regencies and the Majority were closely accompanied by the study and explanation of the forms of life and the planet found in the past.
Petrifying the nation: paleontology collections in Brazil, 1836-1844
Keywords: história ambiental; Império do Brasil; Peter Wilhelm Lund (1801-1880); museu; paleontologia; environmental history; Brazilian Empire; Peter Wilhelm Lund (1801-1880); museums; paleontology